Pemanfaatan Google Spreadsheet Untuk Akuisisi Data Online Bagi Guru SMK di Banda Aceh - Dirhamsyah, Muhammad; Away, Yuwaldi; Muslimsyah; Jamil, M.; Putra, T. Edisah; Ibrahim, Masri; Novandri, Andri (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
Data acquisition is the process of collecting data or information from various sources, including sensors, software, hardware, or humans, for use in analysis or decision-making. The purpose of data acquisition is to collect data that is accurate, reliable, and useful for further analysis or decision-making. In introducing the concept of data acquisition, acquisition introduction training was conducted for the teaching staff. Data acquisition training covers the process of transferring data from sensors to Google Sheets. For teaching staff at SMK Negeri 2 Banda Aceh, the use of Google Spreadsheets is still too common. Therefore, the community service team successfully carried out training activities on Wednesday, April 13, 2022. The training included an introduction to the ESP8266 microcontroller, then continued with the introduction of Google Spreadsheets, taught how to assemble hardware in the form of DHT11 sensors and ESP8266 microcontrollers, and carried out the process sending data as well as storing data on Google Sheets. This activity has a positive impact on improving the ability of teaching staff and indirectly can be applied in teaching materials or applied in everyday life.